Case study of cascading failure models on temporal variations of the power network - Verma Nishant (2017)
Modern day power systems are becoming more and more complex and this has resulted in the increased vulnerability of these systems. Understanding the mechanism by which cascading outages propagate is challenging. Power system network failures often bring about devastating effects on our personal and professional lives. Therefore, failure regularity and reliability issues of power system networks are primary concerns for researchers of power systems. The project is a case study for cascading failures that occur in the power system. The reasons for cascading failures and its impact on the system is studied. The variation of generation and loads in the power system often brings about drastic changes in the system. Hence, the project deals with the temporal variations of generation units and loads connected to the system. Different cases of first and second order contingencies due to generator outages and line outages were simulated and corresponding limit violations of voltage and power were scrutinized. The simulation results of these cases list down major contingencies that could occur due to a disturbance created by generators or line outages. The system stability was examined and methods for improving the system stability by reactive power compensation are proposed. Major contingencies were ranked based on its severity and then tackled by means of reactive power compensation.